2014
DOI: 10.1155/2014/694934
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Formulation of Turmerone-Rich Hexane Fractions fromCurcuma longaEnhances Their Antileishmanial Activity

Abstract: Promastigote forms of Leishmania amazonensis were treated with different concentrations of two fractions of Curcuma longa cortex rich in turmerones and their respective liposomal formulations in order to evaluate growth inhibition and the minimal inhibitory concentration (MIC). In addition, cellular alterations of treated promastigotes were investigated under transmission and scanning electron microscopies. LipoRHIC and LipoRHIWC presented lower MIC, 5.5 and 12.5 μg/mL, when compared to nonencapsulated fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…A number of these chemical components have established pharmacological potentials. Typically, 2,4-bis (1,1-dimethylethyl)-phenol found in both the subfractions is reported to possess anti-inflammatory (Amaral et al 2014;Chandrasekar et al 2015;Kumar, Bhatnagar & Srivastava 2011;Yogeswari et al 2012), neuronal and antioxidant (Yang et al 2016) effects. The 2,4-di-tert-butylphenol plays a significant role as an antioxidant and marine metabolite (NLM 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A number of these chemical components have established pharmacological potentials. Typically, 2,4-bis (1,1-dimethylethyl)-phenol found in both the subfractions is reported to possess anti-inflammatory (Amaral et al 2014;Chandrasekar et al 2015;Kumar, Bhatnagar & Srivastava 2011;Yogeswari et al 2012), neuronal and antioxidant (Yang et al 2016) effects. The 2,4-di-tert-butylphenol plays a significant role as an antioxidant and marine metabolite (NLM 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The GC MS patterns revealed peaks that represented (5-octadecene, (E-phenol,2,4-bis (1,1 dimethylethyl; 1-Nonadecene; 1-Eicosanol; 1-Docosene and podocarp-7-en-3-one, 13‫-ב‬methyl-13-vinyl-). The antibacterial, antifungal and anti-inflammatory activities of phenol, 2,4bis (1,1-dimethylethyl)-have previously been reported 30,31 . 1-nonadecene extracted from the Streptomyces sp.…”
Section: Chemical Characterization Of the Ethyl Acetate Extractmentioning
confidence: 96%
“…To study the effect of temperature on the production of antimicrobial agents, isolate Streptomyces sp. MK388207 (M12) was inoculated into 100 mL of the culture formula obtained from the experimental design and incubated at different temperatures (20,25,30,35,40 and 50°C) for 7 days. Supernatant from each experiment was tested using the method of agar well diffusion agai nst C.albicans ATCC 10231 12 .…”
Section: Effect Of Temperature On the Production Of Antimicrobial Agentsmentioning
confidence: 99%
“…Chandrasekar et al [23] showed that NimbapatradiChoornam had strong antimicrobial activity against Klebsiella pneumoniae, S. aureus, E. coli and Candida albican. The presence of phenol, 2,4-bis[1,1-dimethylethyl]-derivative, isopropyl myristate, eicosane, octadecanoic acid and hexadecanoic acid compounds were responsible for the antimicrobial activity of Nimbadipatrachoornam.…”
Section: Production Of Antibacterial Compound and Gc-ms Analysismentioning
confidence: 99%